Global changes in DNA methylation in seeds and seedlings of Pyrus communis after seed desiccation and storage. - Marcin Michalak; Mirosława Z Barciszewska; Jan Barciszewski; Beata P Plitta; Paweł Chmielarz (PLoS ONE, 2013)
The effects of storage and deep desiccation on structural changes of DNA in orthodox seeds are poorly characterized. In this study we analyzed the 5-methylcytosine (m(5)C) global content of DNA isolated from seeds of common pear (Pyrus communis L.) that had been subjected to extreme desiccation, and the seedlings derived from these seeds. Germination and seedling emergence tests were applied to determine seed viability after their desiccation. In parallel, analysis of the global content of m(5)C in dried seeds and DNA of seedlings obtained from such seeds was performed with a 2D TLC method. Desiccation of fresh seeds to 5.3% moisture content (mc) resulted in a slight reduction of DNA methylation, whereas severe desiccation down to 2-3% mc increased DNA methylation. Strong desiccation of seeds resulted in the subsequent generation of seedlings of shorter height. A 1-year period of seed storage induced a significant increase in the level of DNA methylation in seeds. It is possible that alterations in the m(5)C content of DNA in strongly desiccated pear seeds reflect a reaction of desiccation-tolerant (orthodox) seeds to severe desiccation. Epigenetic changes were observed not only in severely desiccated seeds but also in 3-month old seedlings obtained from these seeds. With regard to seed storage practices, epigenetic assessment could be used by gene banks for early detection of structural changes in the DNA of stored seeds.